Current Methods for Extraction and Concentration of Foodborne Bacteria with Glycan-Coated Magnetic Nanoparticles: A Review - Emma Dester; Evangelyn Alocilja (Biosensors, 2022)
Rapid and accurate food pathogen detection is an essential step to preventing foodborne illnesses. Before detection, removal of bacteria from the food matrix and concentration to detectable levels are often essential steps. Although many reviews discuss rapid concentration methods for foodborne pathogens, the use of glycan-coated magnetic nanoparticles (MNPs) is often omitted. This review seeks to analyze the potential of this technique as a rapid and cost-effective solution for concentration of bacteria directly from foods. The primary focus is the mechanism of glycan-coated MNP binding, as well as its current applications in concentration of foodborne pathogens. First, a background on the synthesis, properties, and applications of MNPs is provided. Second, synthesis of glycan-coated particles and their theorized mechanism for bacterial adhesion is described. Existing research into extraction of bacteria directly from food matrices is also analyzed. Finally, glycan-coated MNPs are compared to the magnetic separation technique of immunomagnetic separation (IMS) in terms of cost, time, and other factors. At its current state, glycan-coated MNPs require more research to fully identify the mechanism, potential for optimization, and extraction capabilities directly in food matrices. However, current research indicates glycan-coated MNPs are an incredibly cost-effective method for rapid food pathogen extraction and concentration.